Long term changes in phospho-APP and tau aggregation in the 3xTg-AD mice following cerebral ischemia - Koike, MA (2011)
The risk of Alzheimer’s disease increases following cerebral hypoperfusion. We studied the long-term interaction between low blood flow to the brain and Alzheimer’s disease by inducing a transient global ischemic insult in aged 3xTg-AD mice and determining the effects on AD pathology 3-months post injury. We found that global ischemia does not increase the levels of amyloid-β in these mice. However, the injury did lead to enhanced phosphorylation of the amyloid precursor protein (APP) at the Thr668 site in both the 3xTg-AD mice and wild-type controls. Furthermore, we found an increase in insoluble total tau 3-months post-injury. Together these findings further elucidate the long-term impact of cerebral hypoperfusion on Alzheimer’s disease.